Vitamin A supplementation every 6 months with retinol in 1 million pre-school children in north India: DEVTA, a cluster-randomised trial - Awasthi, S; Pande, V; Peto, R; Read, S; Clark, S; Bundy, D (Elsevier, 2013)
Background In north India, vitamin A deficiency (retinol <0·70 μmol/L) is common in pre-school children and 2-3% die at ages 1·0-6·0 years. We aimed to assess whether periodic vitamin A supplementation could reduce this mortality. Methods Participants in this cluster-randomised trial were pre-school children in the defined catchment areas of 8338 state-staffed village child-care centres (under-5 population 1 million) in 72 administrative blocks. Groups of four neighbouring blocks (clusters) were cluster-randomly allocated in Oxford, UK, between 6-monthly vitamin A (retinol capsule of 200 000 IU retinyl acetate in oil, to be cut and dripped into the child's mouth every 6 months), albendazole (400 mg tablet every 6 months), both, or neither (open control). Analyses of retinol effects are by block (36 vs 36 clusters). The study spanned 5 calendar years, with 11 6-monthly mass-treatment days for all children then aged 6-72 months. Annually, one centre per block was randomly selected and visited by a study team 1-5 months after any trial vitamin A to sample blood (for retinol assay, technically reliable only after mid-study), examine eyes, and interview caregivers. Separately, all 8338 centres were visited every 6 months to monitor pre-school deaths (100 000 visits, 25 000 deaths at ages 1·0-6·0 years [the primary outcome]). This trial is registered at ClinicalTrials.gov, NCT00222547. Findings Estimated compliance with 6-monthly retinol supplements was 86%. Among 2581 versus 2584 children surveyed during the second half of the study, mean plasma retinol was one-sixth higher (0·72 [SE 0·01] vs 0·62 [0·01] μmol/L, increase 0·10 [SE 0·01] μmol/L) and the prevalence of severe deficiency was halved (retinol <0·35 μmol/L 6% vs 13%, decrease 7% [SE 1%]), as was that of Bitot's spots (1·4% vs 3·5%, decrease 2·1% [SE 0·7%]). Comparing the 36 retinol-allocated versus 36 control blocks in analyses of the primary outcome, deaths per child-care centre at ages 1·0-6·0 years during the 5-year study were 3·01 retinol versus 3·15 control (absolute reduction 0·14 [SE 0·11], mortality ratio 0·96, 95% CI 0·89-1·03, p=0·22), suggesting absolute risks of death between ages 1·0 and 6·0 years of approximately 2·5% retinol versus 2·6% control. No specific cause of death was significantly affected. Interpretation DEVTA contradicts the expectation from other trials that vitamin A supplementation would reduce child mortality by 20-30%, but cannot rule out some more modest effect. Meta-analysis of DEVTA plus eight previous randomised trials of supplementation (in various different populations) yielded a weighted average mortality reduction of 11% (95% CI 5-16, p=0·00015), reliably contradicting the hypothesis of no effect. Funding UK Medical Research Council, USAID, World Bank (vitamin A donated by Roche). © 2013 Elsevier Ltd.